More actions are needed to support the biomass power industry in the developing countries. (1st January 2021) - Yang, Limin; Lu, Qian
Highlights: Some problems associated with biomass power industry should be identified and solved. Technology improvement, industry upgrading and government's support are highly needed. Biomass power industry can have a promising prospect in the developing countries.